Current problems of the world economy and international trade - Popkova, Elena G.; Andronova, Inna V. (Research in economic anthropology ;, 2022)
Volume 42 of Research in Economic Anthropology focuses on systemic coverage, critical rethinking, and scientific analysis of the current problems facing the world economy and international trade aiming to provide a scientific basis for learning from the COVID-19 pandemic for the global economy and international trade. Current Problems of the World Economy and International Trade begins by reflecting the impact of the COVID-19 pandemic and the ensuing crisis for the global economy and international trade. The volume then reveals the prospects for the post-pandemic recovery of the world economy and the crisis management of international trade. Throughout, there are case studies from various countries, in particular the experience of China, Pakistan, Russia, Spain, Germany, Turkey, Kazakhstan, Kyrgyzstan, India, and the OECD. Current Problems of the World Economy and International Trade reveals the determinants of competitiveness and drivers of economic growth of individual countries provides useful applied advice on post-crisis recovery and the development of the world economy and international trade in the post-pandemic period.